E-019 Comparison of rabbit models of intracranial atherosclerotic disease. (4th August 2020) - Zabriskie, M; Wang, C; Alexander, M
Abstract : Introduction/Purpose: Intracranial atherosclerotic disease (ICAD) is a leading cause of ischemic stroke. Treatment controversies exist due to limited understanding of its pathophysiologic drivers. This results from a paucity of histopathological data from human lesions. Development of an animal model would allow for preclinical studies. This study seeks to characterize development of ICAD in Watanabe heritable hyperlipidemic (WHHL) and homozygous apolipoprotein E-knockout (ApoE) rabbits. Materials and Methods: Mature WHHL rabbits, mature ApoE rabbits fed a high cholesterol diet for up to six months, and juvenile wild-type New Zealand White (NZW) rabbits serving as normal controls underwent the same euthanasia protocol using perfusion fixation, with perfusate delivered through a vascular sheath inserted into a carotid artery. Animals were decapitated and the brain and intracranial arteries harvested and placed in a container with formalin. After two weeks, specimens were sliced to maximize cross-sectional orientation of the proximal intracranial arteries. Light microscopic analysis was performed by a specialized veterinary pathologist after hematoxylin and eosin staining to assess presence of ICAD. Basilar and internal carotid artery segments were each rated as having no, mild, moderate, or advanced ICAD. Two-tailed t-tests were performed to compare disease prevalence among rabbit types. Results: 17 rabbits underwent evaluation, including 5 WHHL (24.3–31.6 months at euthanasia, mean 27.4 ± 2.8), 4 ApoE (37.8–46.8 months, mean 42.8 ± 4.2), and 8 NZW rabbits (6.1–20.9 months, mean 11.1 ± 5.2). In WHHL animals, 5 (33.3%) vessel segments had ICAD on pathology (2 mild, 2 moderate, 1 severe), while 6 (50.0%) ApoE vessel segments had lesions (5 mild, 1 moderate). No lesions occurred in NZW animals. Two-tailed t-tests confirmed lesion occurrence more frequently in model animals (p<0.001). There was no statistical difference in disease occurrence between WHHL and ApoE animals (p=0.178). The observed presence of more advanced disease noted in WHHL rabbits compared to ApoE rabbits was not statistically significant (p=0.296). Conclusion: ICAD can be reliably produced in rabbit models. Mature ApoE rabbits demonstrated less advanced ICAD after short term exposure to a hyperlipidemic diet compared to WHHL counterparts. Further analysis is needed to better characterize development and progression of disease in ApoE rabbits. Disclosures: M. Zabriskie: None. C. Wang: None. M. Alexander: None.